Risk Factors Associated With Mortality After Roux-en-Y Gastric Bypass Surgery - Benotti, Peter (2014)
OBJECTIVE: We sought to identify the major risk factors associated with mortality in Roux-en-Y gastric bypass (RYGB) surgery. BACKGROUND: Bariatric surgery has become an established treatment for extreme obesity. Bariatric surgery mortality has steadily declined with current rates of less than 0.5%. However, significant variation in the mortality rates has been reported for specific patient cohorts and among bariatric centers. METHODS: Clinical outcome data from 185,315 bariatric surgery patients from the Bariatric Outcome Longitudinal Database were reviewed. Of these, 157,559 patients had either documented 30 or more day follow-up data, including mortality. Multiple demographic, socioeconomic, and clinical factors were analyzed by univariate analysis for their association with 30-day mortality after gastric bypass. Variables found to be significant were entered into a multiple logistic regression model to identify factors independently associated with 30-day mortality. On the basis of these results, a RYGB mortality risk score was developed. RESULTS: The overall 30-day mortality rate for the entire bariatric surgery cohort was 0.1%. Of the 81,751 RYGB patients, the mortality rate was 0.15%. Factors significantly associated with 30-day gastric bypass mortality included increasing body mass index (BMI) (P < 0.0001), increasing age (P < 0.005), male gender (P < 0.001), pulmonary hypertension (P < 0.0001), congestive heart failure (P = 0.0008), and liver disease (P = 0.038). When the RYGB risk score was applied, a significant trend (P < 0.0001) between increasing risk score and mortality rate is found. CONCLUSIONS: Increasing BMI, increasing age, male gender, pulmonary hypertension, congestive heart failure, and liver disease are risk factors for 30-day mortality after RYGB. The RYGB risk score can be used to determine patients at greater risk for mortality after RYGB surgery.